Impact of left atrial appendage morphology on indication and procedural outcome after interventional occlusion: results from the prospective multicentre German LAARGE registry - Fastner, Christian; Akın, Ibrahim (EuroIntervention, 2018)
The Official Journal of EuroPCR and the European Association of Percutaneous Cardiovascular Interventions (EAPCI)
Gesehen am 01.10.2020